Activation of Toll-Like Receptors and Inflammasome Complexes in the Diabetic Cardiomyopathy-Associated Inflammation - J. Fuentes-Antrás; A. M. Ioan; J. Tuñón; J. Egido; Ó. Lorenzo (International Journal of Endocrinology)
Diabetic cardiomyopathy is defined as a ventricular dysfunction initiated by alterations in cardiac energy substrates in the absence of coronary artery disease and hypertension. Hyperglycemia, hyperlipidemia, and insulin resistance are major inducers of the chronic low-grade inflammatory state that characterizes the diabetic heart. Cardiac Toll-like receptors and inflammasome complexes may be key inducers for inflammation probably through NF-κB activation and ROS overproduction. However, metabolic dysregulated factors such as peroxisome proliferator-activated receptors and sirtuins may serve as therapeutic targets to control this response by mitigating both Toll-like receptors and inflammasome signaling.